Alternative dispute resolution in Islamic finance: What’s next? / Rafidah Mohd Azli... [et al.] - Mohd Azli, Rafidah; Pauzi, Nasif Sidque; Ubaidah, Ahmad Faiz; Sharif, Dziauddin; Yakob, Mohd Asmadi; Jamil, Hajah MakiahTussaripah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
In Islamic transaction, the disputations between two or more parties could affect the roles and responsibilities. Furthermore, when the court received a case from disputed parties, there will be a perception among each of parties of win-lose situation, whereby one party embellished with satisfaction, while the other party will beat in suffering, so the impact is the relationship between two parties are become farther. Therefore, alternative dispute resolution (ADR) in Islamic Finance is suggested in by many Muslim economist and legal experts as a substitute to any further legal activities. This is because it will satisfy many of litigants and it provides a complementary substitute to litigation. The study about ADR in Islamic finance has been done by previous literature. By the way, the implementation of ADR in Islamic financial institutions still needs to be elaborated. Therefore, this paper aims to discuss about updated issues and challenges of implementations of ADR in Islamic finance. This paper found that the ADR in Islamic finance need a model to make the ADR more flexible and eligible with different kinds of conflicts.